Controversy In The Appointment Of Flexed On And Its Semantic Effect In The Interpretation Of The Koranic Text - Yousif Nasrallah, Myaad (Opción, 2019)
The research aims to show that the difference of interpreters in any phenomenon of grammar was not to prejudice and intolerance, but to understand the meaning of the Koran, by showing the compatibility and interdependence between the texts, which achieve linguistic communication, which is the main function of the language, as the significance of their goal. The research plan was based on an introduction, an introduction and two topics. The first topic: the difference in the appointment of the teacher in the context of verbal (script). That is, attracting more than one contextual element in as- signing the object to it. The second topic: the difference in the appointment of the matafaf between the word and the appreciation, that is, the attraction of the word (context) and the appreciation in the appointment of the deceased It is important to study the appointment of the deceased in two ways: The first is to demonstrate the importance of the contextual relationship be- tween the muluf and the hymn in shaping the meaning of the Qur’anic sen- tence. Language text is a structured structure that includes relationships governed by congruence and coherence, which achieve linguistic communication, which is the main function of language. And the other - the disclosure of the proficiency of the interpreters and their diligence in estimating the damage to it, and the impact of this estimate in the acquisition of implied connotations The research plan was based on an introduction, an introduction and two topics. Introduction: The variation of the orientation of the grammarians in the door of kindness on the part of the grammatical work on the orientation of some interpreters, which falls within the principles of the text and its concept. The first topic: the difference in the appointment of the teacher in the con- text of verbal (script). It includes the effect of the interpreter (the recipient) in showing the internal interrelationship between the texts with his experi- ence and interpretive culture. Therefore, the connotations derived from the text differ according to the understanding of contextual relations. The second topic: the difference in the appointment of the matafaf between the word and appreciation. It is concerned with the difference between the interpreters in the assignment of the murtuf between the word (verbal con- text), and the appreciation, ie, the attraction of the word (context) and the appreciation in the appointment of the deceased.